Production and Characterization of Phospholipases C from some Bacillus thuringiensis Isolates Recovered from Egyptian Soil - Elleboudy, Nooran Sherif; ElKhatib, Walid Faisal; Aboulwafa, Mohammad Mabrouk; Hassouna, Nadia Abdel-Haleem (International Journal of Biotechnology for Wellness Industries, 2016)
Two hundred and thirty one isolates, with the characteristic morphology of Genus Bacillus, were recovered from 100 soil samples collected from 7 different Egyptian governorates, and were screened for phospholipase C (PLC) production by egg-yolk plate method. Sixty isolates have shown very high PLC production and were further assessed using chromogenic assay method. The highest five producers, identified by 16S rRNA gene sequencing as Bacillus thuringiensis, were selected and their PLCs were purified to homogeneity using ammonium sulfate precipitation and Sephadex G-75 gel filtration chromatography. PLCs had molecular masses of 28.5 kDa as indicated by SDS-PAGE. The characteristics of the studied five PLCs were having maximal activities at 35-45°C and pH 7.2. The enzymes could retain more than half of their maximum activities at 30-60°C and pH 7-8. Equivalent activities were recorded at low water tension. PLC from B. thuringiensis KT159186 was relatively thermostable with a maximum activity at 40°C. The half-inactivation temperature was above 50°C, which compared favorably to that of other enzymes. Activity at the wide temperature range (20-80°C) was high (about 50% of maximum),. This PLC could tolerate pH as high as 12 with only 30% loss of activity. Specificity pattern of PLC from the same isolate showed equivalent activities toward phosphatidylcholine and phosphatidylinositol in addition to marked activity toward phosphatidylethanolamine, which makes it a typical non-specific PLC for industrial purposes. In conclusion, these characteristics of PLC from the test isolate make it attractive for various industrial applications.